Clinical approach to the treatment of painful diabetic neuropathy - Alexandra Hovaguimian; Christopher H. Gibbons (Therapeutic Advances in Endocrinology and Metabolism, 2011)
Painful neuropathy is a common and often progressive complication of diabetes. Patients frequently report symptoms of tingling, burning, lancinating pain, hyperesthesia, and allodynia. The natural history of the disease may vary from intermittent mild symptoms to severe chronic daily pain; the latter is often associated with diminished quality of life. There are a variety of pharmaceutical agents from different medicinal categories available for the symptomatic treatment of painful diabetic neuropathy, however selecting an agent is often challenging given the breadth of choices and lack of consistent guidelines. As a result, many patients remain untreated or undertreated. This article presents a practical clinical approach to the treatment of pain in diabetic neuropathy. Recommendations for first-, second-, and third-line medications are based on specific evidence for the treatment of painful diabetic neuropathy as well as safety, tolerability, drug interactions, and cost. Additional topics of discussion include breakthrough pain, opioid use, and topical therapies. This review does not comprehensively discuss all possible treatments for painful neuropathy, but provides a systematic approach designed to guide clinicians in tailoring therapies to the individual patient.